Factor structure of Urdu version of the flourishing scale - Riaz, Fahad; Al-Woraf, Yaser M.; Akram, Bushra; Ahmed, Mirza A.; ul Haq, Muhammad Anwar; Mehmood Khan, Tahir; U. Rehman, Inayat; Barki, Nadia; Munawar, Khadeeja; Kamal, Anila; Kassab, Yaman W.; Bakrin, Faizah S.; et al. (Frontiers Media S.A., 2018)
Background: A great deal of research has been carried out on the assessment of the eudaimonic perspective of psychological well-being and the hedonic perspective of subjective well-being. The Flourishing Scale (FS) has been extensively used in research and practice, as it assesses the fundamental aspects of social psychological functioning. Nevertheless, the psychometric properties of Urdu versions of eudaimonic measures, such as the FS, have not yet been ascertained. The translation and validation of the FS in the Urdu language was not available, and hence this study was planned with the aim to validate the Urdu version of the FS.